2007
DOI: 10.1080/15022250701372099
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Theory: The Need for a Convenor. The Case of Billund

Abstract: A flagship attraction is defined as an attraction that forms a basis for a local or regional development of the tourism industry which otherwise would have existed to a much smaller degree. This paper examines that statement by a study of Legoland as a flagship attraction of Billund as a destination. Interviews have been undertaken with visitors to Legoland, entrepreneurs and different stakeholders within the destination. A stakeholder theory has been used to discuss the question of how to manage a destination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…This finding is intuitively understandable and supports other studies that have shown differences in salience among stakeholders in destinations (Nilsson and Aring, 2007;Sheehan and Ritchie, 2005) and in the degree of involvement between stakeholder segments (Byrd and Gustke, 2007). The results of a study in Queensland indicate a moderate correlation between the perceptions of stakeholders of other's salience and their network position (Coo- , 2009).…”
Section: Understanding Existing Networksupporting
confidence: 78%
“…This finding is intuitively understandable and supports other studies that have shown differences in salience among stakeholders in destinations (Nilsson and Aring, 2007;Sheehan and Ritchie, 2005) and in the degree of involvement between stakeholder segments (Byrd and Gustke, 2007). The results of a study in Queensland indicate a moderate correlation between the perceptions of stakeholders of other's salience and their network position (Coo- , 2009).…”
Section: Understanding Existing Networksupporting
confidence: 78%
“…Tourism destination planning depends on involvement from stakeholders representing public sector, tourism industry, local residents as well as special interest groups for example regarding hunting, yachting or trekking. A stakeholder has the capacity to participate in the process and can see that individual and/or mutual benefits might be derived from the process (Freeman, 1984;Gray, 1989;Terpstra and Simonin, 1993;Jamal and Getz, 1994;Timur and Getz, 2002;Getz and Nilsson 2004;Aas et al, 2005;Nilsson, 2007).…”
Section: Growing Interest For Wildlife Experiencesmentioning
confidence: 98%
“…Sauter and Leisen (1999) discuss stakeholder theory and its application as a normative planning model to managing stakeholders in sustainable development efforts. Jamal and Getz drew up some guidelines in 1995 using stakeholder theory for tourism destination while Nilsson (2007) uses a case study of Billund (home to Legoland) to discuss the question of how to manage a destination dominated by a flagship attraction.…”
Section: Literature Reviewmentioning
confidence: 99%